Economic Impacts of World Trade Organization Policies on Global Market Dynamics: An Econometric Perspective - Hendarto, Totok; Sudjono; Fatmawati, Endang; Judijanto, Loso; Sukomardojo, Tekat (GoAcademica Research & Publishing, 2024)
This study embarks on an in-depth econometric analysis to unravel the economic impacts of World Trade Organization (WTO) policies on global market dynamics. Anchored in a robust quantitative framework, the research meticulously evaluates the extent to which WTO policies have influenced international trade patterns, market volatility, and economic growth across various regions. Utilizing a comprehensive dataset spanning multiple decades, the study employs advanced econometric techniques to dissect the intricate relationship between trade policies and global economic indicators. The findings reveal a nuanced interplay between WTO policies and market dynamics, highlighting significant variations in impact across different economic sectors and geographical regions. The analysis further delves into the implications of these policies on emerging economies, contrasting them with their effects on developed nations. The study concludes with critical insights into the role of WTO in shaping global economic landscapes, offering valuable implications for policymakers and stakeholders in international trade. This research contributes to the broader understanding of global economic interdependencies in the context of WTO policies, providing a foundation for future policy formulation and economic forecasting.